Sistem Pendukung Keputusan Kelayakan Pemberian SIM (Surat Izin Mengemudi) Kepada Pengendara Sepeda Motor Dengan Menggunakan Metode Simple Additive Weighting (Studi Kasus:Polres Kab.Labuhan Batu) - Barany Fachri; Jurais Al Qorni Dalimunthe (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Labuhan Batu District Police Station is a Resort Police office whose job is to serve the community. One of the services is the making of a driver's license. The process of making a driver's license is still done manually, such as filling out the application form and assessing the value of the driving license. The system used in the operational activities of making driving licenses is not optimal, because it is still done manually, therefore a decision support system is needed in determining the passing of the driving license exam so that the assessment process will be more objective and efficient. In that system the applicant must register first, then the applicant can take a theory and practice exam. And testers will judge based on existing criteria. The results of the assessment will be obtained by the applicant as evidence of the results of the exam. For this reason, the author applies the Simple Additive Weighting (SAW) method in the Decision Support System for Graduation of Driving License Tests at the LabuhanBatu District Police Station. Keywords: Manual, System, Objective, Efficient